Gout - Hanan Abdel Rehim (SpringerOpen, 2014)
Gout is a crystal deposition disease caused by raised levels of uric acid in the blood (hyperuricaemia) with persistence of hyperuricemia at levels higher than a serum saturation of 6.8 mg/dl leads to formation of monosodium urate (MSU) crystals and their deposition in joints and other tissues. However, only a minority of individuals with elevated serum uric acid (sUA) levels ever develop gout, emphasizing the importance of other factors in determining crystal formation including Genetics, Gender, age, Diet and alcohol intake, Obesity, some medications and medical conditions a correct diagnosis of gout is essential for the appropriate management, in 2011 the European League Against Rheumatism (EULAR) published an updated evidence based recommendations for diagnosis of gout. Although gout is well understood condition and good therapeutic options are available, it tends to be poorly managed, so The 2012 The American College of Rheumatology (ACR) guidelines for Management of Gout were designed to emphasize safety and quality of therapy and to reflect best practice. New approaches to urate lowering have led to mechanism-based therapies such as: non-purine, selective inhibitor of xanthine oxidase, URAT-1 inhibitors and a recombinant chimeric mammalian uricase. Three IL-1β antagonists - anakinra, rilonacept and canakinumab are being evaluated as an emerging therapies for gout.